2020
DOI: 10.1002/term.3140
|View full text |Cite
|
Sign up to set email alerts
|

Phlorotannins ameliorate extracellular matrix production in human vocal fold fibroblasts and prevent vocal fold fibrosis via aerosol inhalation in a laser‐induced fibrosis model

Abstract: Vocal fold fibrosis is an abnormal condition characterized by unfavorable changes in the organization of the extracellular matrix in vocal fold lamina propria. To prevent and treat vocal fold fibrosis, a number of synthetic drugs, such as mitomycin C and the glucocorticoid family, are used after surgery, but these are known to have some side effects. Therefore, using both in vitro and in vivo studies, this study investigated whether phlorotannins extracted from Ecklonia cava have the potential to prevent vocal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…Biomedical engineering (BME) is a rapidly developing field of medical and biological research that provides new concepts and strategies for the diagnosis, treatment, and prevention of various diseases [ 82 , 83 , 84 ]. The main goal of BME is the development and application of new therapies and technologies to support, repair, or replace damaged cells, tissues, and organs with alternative systems of a bio-artificial nature [ 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…Biomedical engineering (BME) is a rapidly developing field of medical and biological research that provides new concepts and strategies for the diagnosis, treatment, and prevention of various diseases [ 82 , 83 , 84 ]. The main goal of BME is the development and application of new therapies and technologies to support, repair, or replace damaged cells, tissues, and organs with alternative systems of a bio-artificial nature [ 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…This can be attributed to extract concentration into the mesh, which can exceed the maximum safe dose, since other authors reported that phlorotannins are safe and can enhance human trachea fibroblast at concentrations of 25 and 50 µg•mL [94]. Other similar studies also revealed that increasing the phlorotannins concentration between 31.25 and 250 µg•mL does not cause adverse effects on human vocal fold fibroblasts [95]. The other conditions, especially WOE meshes (only with gelatin and chitosan) almost reached the same values as the control of viable cells, without statistical differences (p > 0.05).…”
Section: Cytotoxicitymentioning
confidence: 96%
“…Ph was extracted as previously described by Kim et al. (2020) with slight modifications. Briefly, E. cava was washed three times with tap water to remove epiphytes, salt, and sand attached to the surface and was carefully rinsed again with fresh water.…”
Section: Materials and Methosmentioning
confidence: 99%
“…Phs encompass a unique polyphenolic compound group extracted from brown algae and consist of various phloroglucinol units including eckol, phlorofucofuroeckol A, 6,6′‐bioeckol, and dieckol (Lee et al., 2020; Park et al., 2018). These compounds have garnered increasing attention in biomedical engineering due to their many pharmaceutical effects, as well as anti‐oxidative, anti‐inflammatory, anti‐bacterial, and anti‐fibrotic properties (Catarino et al., 2019; Kim et al., 2020). Furthermore, Phs play an important role in the defense system of brown algae, inhibiting the growth of benthic microorganisms on its blades (Kim et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation